2008
DOI: 10.1111/j.1440-1819.2008.01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Trait aggression in suicide attempters: A pilot study

Abstract: Suicide attempt is a potent risk factor of subsequent suicide. Understanding the characteristics of suicide attempters is important for preventing suicide. The authors investigated aggression in medically serious suicide attempters at an emergency department. Trait aggression was evaluated in 55 suicide attempters and 71 healthy individuals as a control group using the Japanese version of the Buss-Perry Aggression Questionnaire (BAQ). Total BAQ scores (t = 2.782, P = 0.006) and the hostility scores (t = 3.735,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…On the other hand, we have previously reported that those with low serotonin 1A BP F —the opposite of what we found here—have greater aggression, 59 found in some studies to be linked to more lethal suicidal behavior. 60,61 Our sample had relatively low aggression (mean score, 18.5), perhaps indicating that aggression was not a key driver of suicidal behavior for this study population.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, we have previously reported that those with low serotonin 1A BP F —the opposite of what we found here—have greater aggression, 59 found in some studies to be linked to more lethal suicidal behavior. 60,61 Our sample had relatively low aggression (mean score, 18.5), perhaps indicating that aggression was not a key driver of suicidal behavior for this study population.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have highlighted the importance of aggression and related concepts to SSAs. Doihara et al ( 30 ) studied the aggression dimension in 55 MSSA attempters in a hospital’s emergency room, and compared them with a control group of 71 healthy individuals. It was found that aggression and hostility scores were significantly higher in the SSA attempters when compared with controls.…”
Section: Resultsmentioning
confidence: 99%
“…One of them compared medically serious suicide attempters (MSSAs) to healthy controls. Trait aggression was significantly higher in the MSA group, 53 however, that study did not include a non-medically serious suicide attempters (NMSSAs) control group. In another study designated to look for differences among those with specific psychiatric pathologies, personality-disordered individuals, particularly those who are more impulsive and aggressive and who have a co-morbid depressive disorder were found to have a higher risk for more frequent and more medically-severe suicidal behavior in comparison to individuals with Major Depressive Disorder (MDD) or Bipolar Depression (BD) alone.…”
Section: Aggressionmentioning
confidence: 92%